Peptide receptor radionuclide therapy for treatment of metastatic neuroendocrine tumors in children. Issue 7 (12th April 2021) - Foster, Jennifer H.; Sher, Andrew; Seghers, Victor; Poston, Jay; Wells, Donald; Delpassand, Ebrahim S.; Potter, Samara; Mahajan, Priya; Venkatramani, Rajkumar
Abstract: Neuroendocrine tumors (NETs) of the pancreas and midgut are extremely rare in children, and patients presenting with metastatic disease have poor survival. Given this rarity, treatments are extrapolated from guidelines for adults with NET. Recent clinical trials in adults with NETs have shown that the addition of peptide receptor radionuclide therapy (PRRT) with 177 Lu‐DOTATATE resulted in a disease control rate of nearly 80%, with minimal side effects. We report our experience using 177 Lu‐DOTATATE to treat two pediatric patients with metastatic NET.